Faktor Yang Berhubungan Dengan Penerapan Pelayanan Prima Perawat Di Ruang Rawat Inap - Tri Anonim; Afiyah Sri Harnany; Maslahatul Inayah (JURNAL KEPERAWATAN MERSI, 2021)
Background: Good carriers that are no longer optimally equipped by nurses can lead to lower in first class operators and also affect people's enjoyment and loyalty to health facilities. The study targets to decide on elements associated with the usefulness of well-known carriers through nurses within inpatient wards.Method: This research design is structured in a descriptive-analytical form with a cross-sectional approach. A sample of 50 was obtained.  The sample is selected on a random basis. Univariate analysis found that carrier utility is important through true nurses, correct supervision, appropriate rewards, correct task layout, excessive motivation.The Results: Bivariate analysis found that there are many factors associated with well-known carrier utility, especially supervisory factors, rewards, task layout, and motivation. The results of the final analysis on multivariate analysis found that motivation is the variable that is most strongly related to the Application of Excellent Services.Conclusion: The study concluded that there is a stronger correlation between supervision, reward, task, and motivation with the usefulness of Excellent Care in Hospital inpatient wards. It is recommended that health facilities should increase the motivation of nurses so that they can be stimulated to offer Excellent Service.